Accident due to Incorrect Selection of Diode Laser Technique in the Treatment of Oral Venous Malformation - Mohamed Mohsen; Guido Migliau; Daniele Pergolini; Umberto Romeo; Gaspare Palaia (Case Reports in Dentistry)
Venous malformation (VM) originates from a congenital venous network disorder, configuring about 40% of the vascular anomalies that occur in the head and neck region. The usage of diode lasers in the treatment of VM is associated with various advantages, such as short operating time and few postoperative complications. Nevertheless, for larger and deeper VM treatment, it may require more than one session for the complete resolution of the lesion. Laser surgery for oral VM may induce heat accumulation due to excessive irradiation causing adverse events postoperatively, including pain and ulcer formation with scarring. In this clinical case, it was recommended to use the leopard technique (LT) to reduce the lesion size, evaluate the remaining unhealed lesion, and apply different laser techniques to obtain the complete resolution of the lesion.